A primer for teaching digital history : ten design principles - Guiliano, Jennifer (Design principles for teaching history., 2022)
"A Primer for Teaching Digital History presents ten design principles integrating history and technology in classrooms. The book seeks to assist teachers in building their competency and competence in digital history. In a digital history classroom, the stories we want to tell can fundamentally interrogate not just what histories are told but how we tell them and who has access to them. A Primer for Teaching Digital History provides overviews of how differing historians articulate and enact their own digital history through classrooms. Examples illustrate how digital history remains tied to the fundamentals of historical scholarship, evidence and argument but also challenge us to think broadly about what the digital means and can be in history. The Primer represents the possibilities enabled by using digital methods and forms of scholarship as they exist in history classrooms from middle school through collegiate contexts today"--